ByTani (Platform Jual Beli Hasil Pertanian Online Berbasis Website) - Pangestu, Citra; Akbar Gozali, Alfian (eProceedings of Applied Science, 2023)
Abstract—Indonesia is one of the second largest agricultural countries in the world after Brazil. Most of Indonesia's population works in agriculture. This sector accounts for 13.28% of gross domestic product in 2021. Indonesia's very strategic location, starting from the geographical side, causes Indonesia to be in a tropical area which has two seasons. These factors make Indonesia very suitable for the agricultural sector. However, the distribution process of rice yields in Indonesia has many obstacles, including the habit of local farmers selling through collectors so that the profit margin obtained is relatively small. In this final project, a solution called ByTani is proposed (a website-based online agricultural trading platform), a trading platform for agricultural products that will connect farmers with buyers directly so that farmers' profits can increase. Based on a survey conducted by the author on March 1, 2022, to farmers in the West Java area, data obtained that 66.7% of farmers have privately owned rice fields. Of all the farmers interviewed, all sold their produce to local collectors in their area. The sale of crops to collectors creates another problem, namely that farmers become dependent on collectors and have narrow sales targets. Meanwhile, 66.7% of farmers stated that the purchase price from collectors was relatively cheap compared to the total costs incurred during the process of planting rice to harvesting. Based on the test results, 68.5% of farmers agree with the problem that the collector's purchase price is quite low. Based on the solutions offered, 73.3% of farmers agree that the ByTani application as an intermediary for selling farmers' crops can help increase the profit of selling rice.Keywords— Indonesia, agriculture, farmers, collectors, application